PSYCHOLOGICAL AND SOCIAL ASPECTS OF INNOVATIONS AND STANDARDIZATION IN EDUCATION - Arpentieva M. R.; Kassymova G.K.; Kosov A.V.; Tyumaseva Z.I.; Shaimardanov R.H.; Elmendeeva L.V.; Minaeva E.I.; Gorgotz O.V. (Scientific Journal of Pedagogy and Economics, 2020)
The purpose of the research is to analyze the processes of innovation in education in the context of the problems of its standardization and individualization. The research method is a theoretical analysis of the problems of innovation in Russian education in the context of the problems of its standardization and individualization. Modern education has become one of the spheres of traditional business. Corporations and enterprises of different levels actively intervene in educational processes. They trying to optimize management processes at the “initial stage”. The selection of professional, corresponding to a certain organizational culture of personnel goes into the formation of these personnel (starting with the university and ending with the average and primary education). At the same time, individuality and human activity in the world of standards and certifications is less and less time and space: compliance or non-compliance with standards, including management standards, creates a new “queering zone”. These people do not want to live for the sake of serving the interests of financial and industrial corporations and their owners. They are on the verge of total social exclusion. Standardization creates a gap between a person as “unique” individuality, a self-managed and active system and a person as a member of a corporation, a “part” of business, production, a passive “cog” of the system. The standardization of education is an important part of its improvement. However, it should be implemented precisely in the modus of improving a person as an individual, partner and professional. Otherwise, since it is being implemented now, it is aimed at the formation and transformation of a person as a labor "resource" or "capital", more or less demanded by modern economies and businesses, as well as their plans (mondialization and reduction of the planet’s population), it clearly leads to the collapse of universities and schools, education, art and science, that is, culture and humanity as a whole. The standardization of education should include a constant increase in its level in accordance with the development of technologies for training and educating people at all levels of education, in any educational situations. In this context, the individualization of education, there is an increase in the quality of education, the requirements for teachers, students and the process and results of education. The task of society, as well as the state and business, is not to destroy education, but to raise it to new heights, relying on the best achievements, and not rejecting them for the sake of the falsely understood "innovation" and "modernity". Education of the present and the future should integrate the transfer of knowledge and skills (cultural transmission) with the processes of development of a person as a creator: a person as a subject of culture is created by it and creates it.